2006
DOI: 10.1002/tie.20093
|View full text |Cite
|
Sign up to set email alerts
|

Bracing for MNC competition through innovative HRM practices: The way ahead for Indian firms

Abstract: With increasing globalization, firms are entering a dynamic world of international business that is marked by liberalization of economic policies in a large number of emerging economies like India. To face the challenge of increasing competition that has resulted from liberalization, Indian organizations have initiated adoption of innovative human resource management practices both critically and constructively to foster creativity and innovation among employees. With the help of 11 in‐depth case studies, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 1 publication
2
47
0
Order By: Relevance
“…In an empirical study, Som (2006) identified several leading Indian companies such as Wipro and Infosys that have adopted innovative HRM practices that are particularly adjusted to the local labor market. These companies' practices may constitute benchmarks for foreign investors, which are less familiar with the conditions for HRM in India.…”
Section: Contributions Limitations and Suggestions For Further Studiesmentioning
confidence: 99%
“…In an empirical study, Som (2006) identified several leading Indian companies such as Wipro and Infosys that have adopted innovative HRM practices that are particularly adjusted to the local labor market. These companies' practices may constitute benchmarks for foreign investors, which are less familiar with the conditions for HRM in India.…”
Section: Contributions Limitations and Suggestions For Further Studiesmentioning
confidence: 99%
“…India was rapidly growing into one of the biggest emerging markets with a huge market potential. Indian firms had to deal with more and more competition internally which also forced them to adapt to this dynamic environment by restructuring and initiating several organisational changes (Som, 2006). There was also a rise in the number of private firms operating in India .…”
Section: Hrm In Indian Firmsmentioning
confidence: 99%
“…The shortage of talent is something Indian firms have to deal with across all sectors and this puts additional pressure on HR professionals in terms of staffing and recruitment. Globally, more and more companies are recognising the worth of Indian workforce (Som, 2006). This has prompted Indian firms to focus more on performance management, pay structures, career progression and incentive schemes.…”
Section: Hrm In Indian Firmsmentioning
confidence: 99%
“…Som (2006) found some common practices that are linked with superior organizational performance: first, linking HR strategies with overall corporate strategies; second, recruitment and selection of a competent and skilled workforce and investment in their career development; third, proactive performance management systems such as employee stock ownership, open and a transparent work atmosphere, and other integration schemes to retain employees in the organization; and, lastly, rightsizing, de-layering and decentralization of organizational processes to enhance employee motivation and morale.…”
Section: Hrm Practices To Improve Firm Performancementioning
confidence: 99%